Resilient and Trustworthy Dynamic Data-driven Application Systems (DDDAS) Services for Crisis Management Environments - Badr, Youakim; Hariri, Salim; AL-Nashif, Youssif; Blasch, Erik (Procedia computer science, 2015)
Future crisis management systems needresilient and trustworthy infrastructures to quickly develop reliable applications and processes, andensure end-to-end security, trust, and privacy. Due to the multiplicity and diversity of involved actors, volumes of data, and heterogeneity of shared information;crisis management systems tend to be highly vulnerable and subjectto unforeseen incidents. As a result, the dependability of crisis management systems can be at risk. This paper presents a cloud-based resilient and trustworthy infrastructure (known as rDaaS) to quickly develop securecrisis management systems. The rDaaSintegrates the Dynamic Data-DrivenApplication Systems (DDDAS) paradigm into a service-oriented architectureover cloud technology andprovidesa set of resilient DDDAS-As-A Service (rDaaS)components to build secure and trusted adaptable crisis processes. The rDaaSalso ensures resilience and security by obfuscating the execution environment andapplying Behavior Software Encryption and Moving Technique Defense. A simulation environment for a nuclear plant crisis managementcase study is illustrated to build resilient and trusted crisis response processes.